Kinetics and Modeling of Anaerobic Digestion Process - Gavala, H.N.; Angelidaki, I.; Ahring, B.K.
Anaerobic digestion modeling started in the early 1970s when the need for design and efficient operation of anaerobic systems became evident.At that time not only was the knowledge about the complex process of anaerobic digestion inadequate but also there were computational limitations. Thus, the first models were very simple and consisted of a limited number of equations. During the past thirty years much research has been conducted on the peculiarities of the process and on the factors that influence it on the one hand while an enormous progress took place in computer science on the other. The combination of both parameters resulted in the development of more and more concise and complex models. In this chapter the most important models found in the literature are described starting from the simplest and oldest to the more recent and complex ones.
Keywords: ANAEROBIC DIGESTION; KINETICS; MODELING